PERSEPSI MASYARAKAT TENTANG MANFAAT BUDAYA DAN KESEHATAN MENGONSUMSI TAMBELO, SIPUT DAN KERANG DI MIMIKA, PAPUA - Hardinsyah Hardinsyah; Agus Sumule; John Letsoin (Jurnal Gizi dan Pangan, 2006)
Some local foods have cultural and health benefits. Mollusca such as tambelo – a mangrove worm, snail and shell (TSS)  contain essential amino acids and micronutrients required  for optimum health.  This study is aimed to analyse the perception of local community at estuary of Mimika on culture and health benefits of consuming the TSS.  For this purpose 158 people of  the 12 estuary villages, which consist of children (1-11 yrs), teenages (12-19 yrs) and adults (>20 yrs)  from both sexes, were selected  as  subjects.  The data collected covers socio-economic of the family, perception of subjects on cultural and health benefits of the TSS, and  ways to consume the TSS. The results showed that the TSS has significant intangible benefits for culture and health of Mimika’s estuary community. In terms of culture, tambelos (Bactronophorus thoracites and Bankia orcutti) are used as a special entry food for local custome rituals; and  both snails (Telecopium telescopiu, Nerita balteata, dan Naqueita capicana) and shells (Geloina cf coaxan dan Geloina, sp) are used  as  a special main menu for lokal costume rituals. In terms of health, the general health benefits of eating TSS is for strengthening and maintaining optimum stamina.  In addition,  Geloina, sp (a shell) is used for wound healing; and  Bactronophorus thoracites (a tambelo), which is called  as “kamoro pil” by Kamoro ethnic, is consumed to have better production of breastmilk, and to have  prevention and theurepetic effects of malaria, cough, flu, rheumatic and backache, as well as  approdisiac and appetite effects. Tambelo is consumed freshly, while snails and shell are steamed or roasted before they are consumed.